Future Regional Tax Predictions in Malang City Using Time Series Method Based on Growth Rates - Damayanti, Made Tara; Puspita, Ayu Fury; Amirya, Mirna (Universitas Negeri Surabaya, 2024)
This research aimed to predict the regional tax potential of Malang City for the period of 2022 to 2026 by using the time series method with a focus on hotel, restaurant, entertainment, and parking taxes. The results showed that these taxes tended to increase annually except for entertainment, suggesting a downward trend. Furthermore, a comparison between potential tax predictions and the realization showed that predictions using the time series method produced figures lower than the actual realization. This discovery was influenced by the post-COVID-19 economic recovery in 2022. The research further showed that the time series method was more suitable for projecting a period of stable economy to produce more accurate projections.